The United States' Entry into World War I and Its Impact on U.S -Canadian Relations (1917-1918). - Jawad Kadhim Dakhil; Ammar Khalid Ramadan ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2026)
This study is of particular importance as it sheds light on an aspect of international politics during a pivotal historical period that marked the beginning of a new chapter in international relations. The United States played a decisive and influential role in shaping global events and in achieving international stability and balance both worldwide and within North America specifically.                                                                                                                           The study aims to examine how American participation in World War I affected bilateral relations with Canada and to explore the nature of these relations following the United States’ entry into the war. The U.S. decision to join the Allied Powers in April 1917 represented a turning point in international history, not only by tipping the scales in favor of the Allies against the Central Powers but also by redefining the nature of U.S.–Canadian relations.                         At that time, Canada remained politically tied to the British Empire, and the United States’ involvement in the war influenced every dimension of bilateral relations economic, military, and diplomatic. Furthermore, it fostered greater opportunities for direct interaction and cooperation between the two nations, reduced Canada’s complete dependence on Britain, and paved the way for a gradual evolution toward independence in Canadian foreign policy in the post-war era.DOI: https://doi.org/10.54633/2333-025-058-017